Contextual Effects in Judgments of Taste Intensity: No Assimilation, Sometimes Contrast. (March 2017) - Shepard, Timothy G.; Shavit, Adam Y.; Veldhuizen, Maria G.; Marks, Lawrence E.
Judgments of taste intensity often show contextual contrast but not assimilation, even though both effects of stimulus context appear in other sense modalities, such as hearing. Four experiments used a paradigm that shifts the stimulus context within a test session in order to seek evidence of assimilation in judgments of the taste intensity of sucrose and, for comparison, the loudness of 500-Hz tones. Experiment 1 found no assimilation in taste using three response scales, magnitude estimation, labeled magnitude, and visual analog, but did find evidence of contrast. Experiments 2 and 3 found no clear evidence of either assimilation or contrast in taste, but found consistent evidence of assimilation in loudness. Experiment 4 found no assimilation in loudness, however, when the intervals between successive stimuli increased from about 6 to 30 s in order to match the interval used with sucrose in Experiments 1 to 3. Taken together, these findings suggest that the assimilation found in intensity judgments in other sensory modalities may not appear in taste perception because of the slower rates presenting of taste stimuli.